Substituição parcial do titânio pelo nióbio em um aço ASTM 409: efeito na microestrutura, textura e estampabilidade - Ricardo José Gonçalves Costa (2017)
The ferritic stainless steel ASTM 409 stabilization in automotive exhaust systems application is increasing, demanding a high stabilization in order to avoid premature intergranular corrosion failures caused by sensitization. Ti is one of the most common elements used to stabilize the ferritic structure. However more elevated Ti content increases the industrial complexity mainly at Melt Shop. Two possible problems are thesubmerged valve obstruction in the Melt Shop and the lamination which is a superficial defect on the cold rolled coils. On this way, the stabilization with Ti+Nb is an alternative to replace part of Ti content for Nb maintaining the same intergranular corrosion resistance. The objective of this study was to investigate the effects of the Ti partial replacement for Nb in the microstructure and recrystallization texture, of the ASTM 409 stainless steel, and correlate them with the mechanical and drawing properties modifications. The results have shown that the addition of Nb leads to a deformed microstructure after hot rolling with a strong Goss component {110}001. In the deformed condition, both steels have shown -fiber. However, the dual-stabilized steel has shown more -fiber intensity.After final annealing, the texture modification, caused by the Nb addition, led to a -fiber increase and a better average coefficient of anisotropy (). Thus, it was demonstrated that the partial replacement of the Ti for Nb in the ASTM 409 stainless steel caused modifications in the recrystallization texture resulting in better drawing properties.